Pengaruh Pengetahuan Tentang Sistem Administrasi Perpajakan dan Modernisasi Administrasi Perpajakan Terhadap Kepatuhan Wajib Pajak Orang Pribadi (Pada KPP Pratama Singosari Kabupaten Malang) - Susilo, Heru; Hidayat, R. Rustam; Arif, Achmad (Jurnal Mahasiswa Perpajakan, 2016)
Taxes for the state help to support the activities of the management of the country, where taxes are used to support the financing of key sectors for the country. For the people of tax can be interpreted as a contribution to the financing process throughout the country all the programs that have been set. Taxes are the main source of income of the state, public or taxpayer compliance and tax administration system that there had been a major supporter in affecting a large number of taxes received by the state. Â  The research objective to be achieved in this research is to determine the amount of influence that the variables in this case that the tax administration system, modernization of tax administration and the tax administration and the modernization of tax administration to compliance of individual taxpayers so that it can be determined variables that have an influence most of the efforts to improve the compliance of taxpayers. Based on the results of data analysis can be seen throughout the study variables significantly influence taxpayer compliance. Keywords: Knowledge Taxpayers About Tax Administration System is applied, the Tax Administration System Modernization and Compliance Mandatory Personal Tax. Â